#TITLE_ALTERNATIVE# - ASHARI (NIM 13600009), MUHAMMAD
This final project is studying structural failure modes namely buckling on thin-walled grooved aluminum tubes using finite element method. Modelling and analysis is are using MSC.Nastran for Windows 4.5 software. The model are Alumunium tubes 60 and 100 mm in diameter with number of groove, n=0,1,2,3,4,5,6,7. The loading is constant displacement. The grooves are mainly for the plastic deformation and control the buckling mode. The aim of final project are to determinethe buckling critical load, Pcr for all models and investigate a Pcr – n curve and observe buckling mode that take place. Then the result from numerical method is compared with ABAQUS software and eksperimental method from previous work. From the compared results, it's found that calculation with NASTRAN, ABAQUS, and experiment are quite close. The reason of choosing model from thin-waled grooved aluminum tubes is all about energy absorbtion.From several research it was found that thin-waled grooved aluminum tubes is the best shape of structure in absorbing impact energy compared with other structure.The more a structure absorb impact energy then damage effect caused by collision also decreasing so that safety may be more guaranteed.